マダラのホスファチジルコリン及びホスファチジルエタノールアミンの消化性 - OHSHIMA, Toshiaki; 大島, 敏明; オオシマ, トシアキ; OSHIMA, Toshiaki; Wada, Shun; 和田, 俊; ワダ, シュン; Koizumi, Chiaki; 小泉, 千秋; コイズミ, チアキ (NIPPON SUISAN GAKKAISHI, 1983)
Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) of cod Gadus morhua were spearated by HPLC and analyzed for the fatty acid compositions and the compositions based on total carbon in fatty acyl chains by GLC. From the results obtained, the possible fatty acid combinations of PC and PE were estimated. Without regard to the number of double bonds in the fatty acid, eight possible fatty acid combinations: (C18, C22), (C18, C20), (C18, C18), (C20, C20), (C20, C22), (C18, C22), (C22, C22), and (C14, C20), were estimated for the PC. The combination of (C16, C22), was most prominent, acounting for 44.2% in the PC. Similarly, nine possible fatty acid combinations: (C18, C22), (C16, C22), (C20, C20), (C20, C22), (C18, C20), (C22, C22), (C14, C22) (C16, C20), and (C18, C18), were estimated for PE. The combination of (C18, C22) was most prominet, accounting for 23.5% in the PE. From the fatty acid compositions, the major fatty acid combinations of PC and PE were tentatively estimated to be as follows: (C16:0, C22:6), (C16:0, C20:5), (C18:1, C18:1), (C20:5, C20:5), (C20:5, C22:6), (C18:1, C22:6), (C22:6, C22:6), and (C14:0, C20:5) for PC and (C18:1, C22:6), (C16:0, C22:6), (C20:5, C20:5), (C20:5, C22:6), (C18:1, C20:5), (C22:6, C22:6), (C14:0, C22:6), (C16:0, C20:5), and (C18:1, C18:1) for PE. journal article